Peran Perguruan Tinggi Melalui Penelitian dan Program Pengabdian Kepada Masyarakat dalam Penanggulangan Bencana di Indonesia - Ibrahim Danuwikarsa (LPPM UNINUS, 2013)
If examined from geography, geology, and demographic, the territory of Republic of Indonesia has a high level of vulnerability to disasters, whether caused by natural factors, the non - natural factors and human factors. Types of disasters in Indonesia are floods, landslides, droughts, forest and land fires, wind storms/cyclones, storm surge/tides, earthquakes, volcanic eruptions, technology failures, tsunamis, and disease epidemic. Disaster management paradigm has shifted, that is no longer emphasizing aspects of emergency responses, but more on the overall disaster risk management. Academicians could take their roles in disaster management through community service program and research: it is implementing disaster risk deduction paradigm, which can be a variety of activities introducing threats to community in the area, how to reduce the hazards and vulnerability, as well as increasing community capacity in facing any threats of disasters.